Risk Analysis in Capital Budgeting Decisions: Sensitivity and Scenario Analysis Approach - Rasid Rasid; Tamrin Tamrin; Dudirianto Dudirianto; Risnayanti Risnayanti; Jusnawati Jusnawati; Dumaria Santia Dewi; Abd. Rasyid; Muchlis Muchlis (JURNAL MANAJEMEN DAN BISNIS, 2025)
Capital budgeting decisions are inherently exposed to uncertainty due to fluctuating economic conditions and imperfect cash flow projections. Inaccurate investment evaluation may lead to significant financial losses and inefficient allocation of organizational resources. This study aims to analyze the role of risk assessment in capital budgeting decisions by applying sensitivity analysis and scenario analysis as complementary evaluation tools. Using a descriptive-analytical approach supported by numerical illustrations, this study examines how changes in key financial variables such as selling price, sales volume, production costs, and discount rates affect project feasibility indicators, particularly Net Present Value (NPV). The findings demonstrate that sensitivity analysis is effective in identifying critical variables with the highest impact on project outcomes, while scenario analysis provides a more comprehensive view of project resilience under varying economic conditions. The study concludes that integrating both methods enhances decision quality, supports proactive risk management, and improves long-term investment sustainability.